Self-knowledge of the mind in Christianity and Buddhism - Stróżyński, Mateusz (Filozofia Chrześcijańska, 2021)
The article compares the understanding of self-knowledge of the mind in Tibetan Buddhism (in the schools of Mahamudra and Dzogchen) with the ancient, Platonic Christian philosophy. It argues that in both traditions there are two aspects of the experience of self-knowledge: the impossibility of grasping the mind as an object and the ceaseless, unavoidable awareness of the mind’s cognitive activity. The fi rst of those aspects is called by the Tibetan tradition “emptiness”, while the second – lucidity of the mind’s nature. In Gregory of Nyssa and Augustine of Hippo we can see a diff erence of accent in terms of the signifi cance of those two motifs, but it seems that both philosophers understand self-knowledge in a very similar way. Recognizing those two aspects is what brings the Buddhist and the Western traditions close to each other, while a fundamental diff erence between them lies in the fact that in the latter, selfknowledge of the mind opens a path to the experience of the infi nite mind of God, of which the fi rst is an image, while in Buddhism the concept of God does not appear at all. Individual self-knowledge is treated as the experience of the nature of one, universal and absolute mind.